REKONDISI BEBERAPA UKURAN TUBUH TERNAK SAPI PERAH FRIESS HOLLAND DI BALAI PENGEMBANGAN BIBIT DAN PAKAN TERNAK TAMPUSU - Maluhima, Renaldo J.; Manopo, J.H.; Lomboan, A.; Turangan, S.H. (ZOOTEC, 2019)
COMPENSATORY CONDITION OF SEVERAL MEASURES IN FRIESS HOLLAND DAIRY CATTLE AT TAMPUSU ANIMAL FEED AND SEED DEVELOPMENT CENTER. This study was conducted to assess the compensatory condition of some body sizes of Friess Holland Dairy Cattle at Tampusu Animal Feed and Seed Development Center. Animals used in this study were 23 Friesian Fries Holland (FH) dairy cattle at aged of 7 months to 7 years old using a comparative descriptive research method by comparing the same variables for different samples and using the t-test. Research was done by measuring body weight, chest circumference, shoulder’s height and body length. The maintenance of animals was using a double cage head to head. Feeds given were using forages of 10% / head / day from body weight. Concentrate was fed about 2 kg / head / day. Dairy cows in Tampusu have an average body weight of 401.533 ± 39.47 Kg with a varince coefficient value of  9.8%, an average chest circumference of 174.12 ± 11.15 cm with a varience coefficient value of 6.4%, average shoulder height 136.47 ± 9.16 cm with a variance coefficient value of 6.7%, average body length 139.39 ± 9.56 vm with a variance coefficient of 6.8%. Based on these results, the compensatory condition friess holland dairy cattle at tampusu animal feed and seed development center was increase   body weight of 11.6%, chest circumference 6.28% and shoulder height of 6.65%. Keywords: Compensatory condition, body measurements, Friess Holland Dairy Cattle